Pengaruh Ekstrak Tembakau terhadap Serangan Rayap Kayu Kering Cryptotermes cynocephalus Light pada Bambu Apus (Gigantochloa apus Kurz) - Sutjipto A Hadikusumo (Fakultas Kehutanan Universitas Gadjah Mada, 2007)
Effect of Tobacco Extracts on Apus Bamboo (Gigantochloa apus Kurz) resistance against Drywood Termite Cryptotermes cynocephalus Light (Gigantochloa apus Kurz) AttacksBamboo is one of community forest products and people use it for many purposes. Due to insect attack such as termite, the life time of bamboo product is short. To avoid chemical pollution in bamboo preservation process, tobacco extract was used.Tobacco was extracted in water, in the amounts of 100, 150 and 200 g in 1 l of water, at temperature of 70-80°C for 3 hours. Bamboo trees were cut, the bottom parts were soaked in tobacco extract solution for 1, 3 and 5 days. Samples were cut into 5 cm x 3 cm x bamboo thickness at the bottom, middle and upper parts of the bamboo tree. After being air dried, each sample was exposed to 50 dry wood termites in a small glass tube for two months.The results showed that bamboo preservation by diffusion with high concentration of tobacco extract (200 g tobacco extracted in 1 l of water) resulted in 61% termite mortality.